Development of a Simple Index to Measure Overuse of Diagnostic Testing at the Hospital Level Using Administrative Data. Issue 2 (20th January 2021) - Ellenbogen, Michael I; Prichett, Laura; Johnson, Pamela T; Brotman, Daniel J
Abstract : OBJECTIVE: We developed a diagnostic overuse index that identifies hospitals with high levels of diagnostic intensity by comparing negative diagnostic testing rates for common diagnoses. METHODS: We prospectively identified candidate overuse metrics, each defined by the percentage of patients with a particular diagnosis who underwent a potentially unnecessary diagnostic test. We used data from seven states participating in the State Inpatient Databases. Candidate metrics were tested for temporal stability and internal consistency. Using mixed‐effects ordinal regression and adjusting for regional and hospital characteristics, we compared results of our index with three Dartmouth health service area‐level utilization metrics and three Medicare county‐level cost metrics. RESULTS: The index was comprised of five metrics with good temporal stability and internal consistency. It correlated with five of the six prespecified overuse measures. Among the Dartmouth metrics, our index correlated most closely with physician reimbursement, with an odds ratio of 2.02 (95% CI, 1.11‐3.66) of being in a higher tertile of the overuse index when comparing tertiles 3 and 1 of this Dartmouth metric. Among the Medicare county‐level metrics, our index correlated most closely with standardized costs of procedures per capita, with an odds ratio of 2.03 (95% CI, 1.21‐3.39) of being in a higher overuse index tertile when comparing tertiles 3 and 1 of this metric. CONCLUSIONS: We developed a novel overuse index that is preliminary in nature. This index is derived from readily available administrative data and shows some promise for measuring overuse of diagnostic testing at the hospital level.